2019
DOI: 10.1111/ijfs.14289
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of electrolysed water and ultrasound to improve the sanitation of knives in the meat industry

Abstract: Summary This study investigated the effect of the combination of basic electrolysed water (BEW) and slightly acid electrolysed water (SAEW) with ultrasound (US) for cleaning and sanitation of the knives used in slaughtering processes. The knives were sonicated in a US bath using two modes of operation (normal and sweep) in two steps: (i) 5 min with BEW and (ii) 10 min with SAEW at 35 °C. The microbiological counts and the possible changes in the physical structure of the knives were evaluated. The association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…At present, BEW is the by-product of acidic electrolyzed water (AEW) which has a wide range of applications in food, agriculture, aquaculture, livestock industries [8] , [9] . Additionally, BEW also possesses excellent functional characteristics, including typically higher pH > 12.0 and redox potential (ORP, −800 to −900 mV) [10] , [11] . More importantly, BEW has a broad-spectrum ability of anti-bacteria and enzyme inactivation, which can effectively prevent the products from degradation [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, BEW is the by-product of acidic electrolyzed water (AEW) which has a wide range of applications in food, agriculture, aquaculture, livestock industries [8] , [9] . Additionally, BEW also possesses excellent functional characteristics, including typically higher pH > 12.0 and redox potential (ORP, −800 to −900 mV) [10] , [11] . More importantly, BEW has a broad-spectrum ability of anti-bacteria and enzyme inactivation, which can effectively prevent the products from degradation [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, BEW has a broad-spectrum ability of anti-bacteria and enzyme inactivation, which can effectively prevent the products from degradation [11] , [12] . Furthermore, its negative redox potential can protect the active groups of proteins from oxidation and improve the quality of end products [10] , [13] . Therefore, there is an urgent need for the development of BEW in food industry.…”
Section: Introductionmentioning
confidence: 99%
“…In literature no other work evaluated the efficacy of REW alone in reducing the microbial load on stainless steel surfaces; other authors evaluated its efficacy in association with SAEW and ultrasound to improve the sanitation of knives in the meat industry, but due to the different treatments applied we could not compare the data (Brasil et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The meat industry faces challenges in removing FOG residues from equipment surfaces (Brasil et al, 2020; Khalid, Ab. Aziz, & Taip, 2020).…”
Section: Fat Oil and Grease (Fog) Residuesmentioning
confidence: 99%
“…These solutions had the potential to replace sodium hypochlorite as a disinfecting agent. However, Brasil et al (2020) investigated the effectiveness of AlEW, followed by sAcEW, for sanitation of the stainless steel surface of meat knives used in slaughtering procedures. The findings indicated that cleaning and disinfecting meat knives were possible using the combination of AlEW followed by sAcEW aided by ultrasound without any changes to the blades.…”
Section: Introductionmentioning
confidence: 99%